INTERNATIONAL ACCREDITATION IN ARCHITECTURE EDUCATION - Harsritanto, Bangun I R (MODUL, 2022)
The UNESCO/International Union of Architects (UIA) Charter for Architectural Education of 2001 recognized the importance of addressing sustainability in educational programs and, in particular, emphasized sensitivity toward the environment and social responsibility. Therefore,  schools’ curricula were analyzed according to their respective architectural program reports, as well as online data from their websites, in order to determine the extent of sustainability education in their programs under the national accreditation of architecture education